Advancing Islamic Education: Fostering Multicultural Values through the Implementation of Islamic Religious Education - Ulumuddin, Ulumuddin; Aisyah, Siti Nur; Hakim, Lukman; Khoir, Abu; Suhermanto, Suhermanto (JURNAL ISLAM NUSANTARA, 2023)
This research aims to analyze the development of Islamic education by implementing the values of Multicultural Islamic religious education in madrasas. The research was conducted using a qualitative approach and a case study type of research. Data collection techniques used participant observation, in-depth interviews, and documentation. The data analysis technique uses the Miles and Huberman model: data display, data reduction, and concluding. The research results show that multicultural Islamic education is a response to the development of population diversity in Islamic educational institutions and demands for equal rights for each group. All students, regardless of groups such as gender, ethnicity, race, culture, social strata and religion, have the right to receive the same education. Implementing Islamic religious education in developing the value of Islamic education institutions at Madrasah Ibtidaiyah Ihyaul Islam Pajarakan includes institutional, curriculum, and personnel aspects. This research provides implications regarding the importance of multicultural values in Islamic education, which can help increase students' awareness and understanding of cultural diversity and universal Islamic values.